Epidemiology, clinical characteristics, diagnosis and vaccination of tick-borne encephalitis: an overview - Navickaitė , G.; Mineikytė , R.; Valaikienė , J. (Neurologijos seminarai, 2018)
The number of diagnosed tick-borne encephalitis in humans has been increasing and the virus can be seen in more geographical locations. There are few reasons for the increasing number of cases which could be attributed to increasing popularity of outdoor activities, tourism in infected areas, and better diagnosis of the disease. Lithuania is among countries in Europe with the absolute highest numbers of documented cases of tick-borne encephalitis. In 2016, the incidence of EE was two times higher than in 2015. Tick-borne encephalitis causes human neurological symptoms. The diagnosis is made more difficult by unspecified symptoms. The only reliable method to prevent TBE is vaccination. This article presents the cycle of the TBEV, distribution, subtypes of the virus, main hosts and host types, clinical characteristics of TBE, diagnostics and vaccination.
Keywords: tick-borne encephalitis; tick-borne encephalitis virus; clinical characteristics; diagnosis; vaccination